Pengaruh Kinerja Keuangan, Kepemilikan Saham Asing, Konsentrasi dan Pertumbuhan Perusahaan terhadap Kualitas Pelaksanaan Tata Kelola Perusahaan - Einde Evana; R. Widdie Andriyanto; Betaria Sylvia H. A. Marbun (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
The background of this research is there are so many research that successfully found the positive influence of corporate governance implementation toward company performance. According to various research about corporate governance, writer interested to do this research with the aim is to look for factors influencing quality of corporate governance implementation of public companies in Indonesia. The sample of this research is public companies in Indonesia, especially companies participated in survey done by IICG on 2001-2004. Based on purposive judgement sampling method, selected 40 public companies from 138 population as a sample of the research, also including on top ten rank based on IICG Rating. The process of data done with Microsoft Excel and Statistical Product and Service Solution (SPSS) version 11.0 with multiple regression in certainty level 90% or error analysis level (á ) 0.10. With multiple regression analysis and probability analysis value 0.10, the result of statistical test state that independent variable (leverage) influential positive and significant toward quality of corporate governance implementation of company, where as variable of foreign stock ownership concentration have positive relationship but not significantly toward quality of corporate governance implementation of company. For variable of company growth not influential positively and significant toward quality corporate governance implementation of company. Based on the whole result of test obtained the summary that quality of corporate governance implementation of public companies in Indonesia still very low because there were other factors influencing corporate governance implementation of company. These situation supported with so many research have done, even by institution or personal to measure the quality of corporate governance in various country and the result in Indonesia always still in low rank and low value for the quality of corporate governance compare with other countries.